The Effect Of Endorphin Massage Combination And Murottal Therapy On Reduction Of Menstrual Pain In Adolescents At Islamic Al Azhaar High School Tulungagung - Candra Wahyuni; Niken Dwi Lusiani (Universitas STRADA Indonesia, 2023)
Menstrual pain is a cramp that occurs during menstruation. Menstrual pain that occurs in young women makes it difficult for young women to concentrate because of the discomfort felt when experiencing menstrual pain (dysmenorrhea). Menstrual pain can be reduced by pharmacological and non-pharmacological measures. Non-pharmacological treatment to reduce menstrual pain including endorphin massage and murottal therapy. This study aims to determine the effect of endorphin massage and murottal therapy on decreasing menstrual pain in young women at Al Azhaar Tulungagung Islamic High School. This study uses an observational analytic research design with an experimental approach. With purposive sampling technique, a sample of 18 respondents was obtained, the independent variable was endorphine massage and murottal therapy and the dependent variable was menstrual pain for young women before and after being given a combination of endorphine massage and murottal therapy. The Wilcoxon test statistic test was used to determine the effect of the two variables. The results of the 18 respondents before the combination treatment of endorphin massage and murottal therapy found that almost all respondents, 15 respondents (83.3%) experienced menstrual pain in the moderate category whereas after the combination of endorphin massage and murottal therapy, almost all respondents were 14 respondents (77.8 %) decreased menstrual pain in the category of no pain. Analysis using Wilcoxon statistical test showed p = 0,000 <0.05 then H0 was rejected and H1 was accepted, which means that there was a combination of endorphin massage and murottal therapy on decreasing menstrual pain in young women at Al Azhaar Tulungagung High School. Endhorphin massage techniques combined with murottal therapy can stimulate the body to release and increase the production of endorphins and encephalins which function to reduce menstrual pain, improve the mental system to reduce violent behavior exhibiting body chemistry.